Designing of overcomplete dictionaries based on DCT and DWT - Qayyum A.; Malik A.S.; Naufal M.; Saad M.; Mazher M.; Abdullah F.; Abdullah T.A.R.B.T. (Institute of Electrical and Electronics Engineers Inc., 2023)
Atoms; Biomedical engineering; Computer vision; Discrete wavelet transforms; Image reconstruction; Stereo image processing; Stereo vision; Students; Wavelet transforms; Computation complexity; Convergence rates; Discrete Cosine Transform(DCT); KSVD; Method of optimal directions; Over-complete dictionaries; Spare Representation; Sparse representation; Discrete cosine transforms